Ureaplasma diversum and Its Membrane-Associated Lipoproteins Activate Inflammatory Genes Through the NF-κB Pathway via Toll-Like Receptor 4 - Santos-Junior, Manoel N.; Rezende, Izadora S.; Souza, Clarissa L. S.; Barbosa, Maysa S.; Campos, Guilherme B.; Brito, Laís F.; Queiroz, Éllunny C.; Barbosa, Elaine N.; Teixeira, Mariana M.; Da Silva, Letícia O.; Silva, Lucas S. C.; Nascimento, Flávia S.; et al. (Frontiers in Microbiology, 2018)
Objectives: Ureaplasma diversum is a pathogen of cows that may cause intense inflammatory responses in the reproductive tract and interfere with bovine reproduction. The aims of this study were to evaluate the immune response of bovine blastocysts and macrophages to U. diversum infection and to evaluate the invasion capacity of this microorganism in bovine blastocysts. Methods: Viable and heat-inactivated U. diversum strains ATCC 49782 and CI-GOTA and their extracted membrane lipoproteins were inoculated in macrophages in the presence or absence of signaling blockers of Toll-like Receptor (TLR) 4, TLR2/4 and Nuclear Factor ΚB (NF-κB). In addition, the same viable U. diversum strains were used to infect bovine blastocysts. RNA was extracted from infected and lipoprotein-exposed macrophages and infected blastocysts and assayed by qPCR to evaluate the expression of Interleukin 1 beta (IL-1β), Tumor Necrosis Factor Alpha (TNF-α), TLR2 and TLR4 genes. U. diversum internalization in blastocysts was followed by confocal microscopy. Results: Both ureaplasma strains and different concentrations of extracted lipoproteins induced a higher gene expression of IL-1, TNF-, TLR2 and TLR4 in macrophages (p<0.05) when compared to non-infected cells. The used blockers inhibited the expression of IL-1β and TNF-α in all treatments. Moreover, U. diversum was able to internalize within blastocysts and induce a higher gene expression of IL-1b and TNF- α when compared to non-infected blastocysts (p<0.05). Conclusions: The obtained results strongly suggest that U. diversum and its lipoproteins interact with TLR4 in a signaling pathway acting via NF-kB signaling to stimulate the inflammatory response. This is the first study to evaluate the in vitro immunological response of macrophages and bovine blastocysts against U. diversum. These results may contribute to a better understanding of the immunomodulatory activity and pathogenicity of this infectious agent.